PARTISIPASI MASYARAKAT PESISIR PADA PENYELENGGARAAN PENDIDIKAN DI SEKOLAH DASAR NEGERI 02 MARUNDA JAKARTA UTARA - Basuki Rahmad (Universitas Negeri Jakarta, 2012)
Objective research that will produce research findings that can be used or followed-up by elements related to the investigation. In this case the researchers conducted a study in coastal areas of Jakarta on matters relating to public participation to education. In this study researchers get research findings that (1) community participation as a facilitator in providing education in primary schools Marunda,(2) community participation as a motivator on the education in state primary schools Marunda, (3) community participation as partners in the education in state primary schools Marunda. These findings are based on the condition of the people who have a background of economic, social, and educational levels. This research hope can give up the educational levels in coastal areas.